2012
DOI: 10.1104/pp.112.199786
|View full text |Cite
|
Sign up to set email alerts
|

The High-Affinity Phosphate Transporter GmPT5 Regulates Phosphate Transport to Nodules and Nodulation in Soybean    

Abstract: Legume biological nitrogen (N) fixation is the most important N source in agroecosystems, but it is also a process requiring a considerable amount of phosphorus (P). Therefore, developing legume varieties with effective N 2 fixation under P-limited conditions could have profound significance for improving agricultural sustainability. We show here that inoculation with effective rhizobial strains enhanced soybean (Glycine max) N 2 fixation and P nutrition in the field as well as in hydroponics. Furthermore, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
161
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 165 publications
(176 citation statements)
references
References 40 publications
2
161
0
3
Order By: Relevance
“…Because Pi deficiency-induced inhibition of SNF is caused by dramatic reductions in the cytosolic Pi pool in nodules, maintenance of an appropriate nodular Pi level represents a critical adaptive strategy for nodules to diminish the adverse effects of Pi deficiency on SNF capacity (6,8,20). In this study, there was an apparent difference between the two symbiotic systems regarding the maintenance of Pi homeostasis in their organs, particularly nodules and roots, for acclimation to low Pi stress.…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…Because Pi deficiency-induced inhibition of SNF is caused by dramatic reductions in the cytosolic Pi pool in nodules, maintenance of an appropriate nodular Pi level represents a critical adaptive strategy for nodules to diminish the adverse effects of Pi deficiency on SNF capacity (6,8,20). In this study, there was an apparent difference between the two symbiotic systems regarding the maintenance of Pi homeostasis in their organs, particularly nodules and roots, for acclimation to low Pi stress.…”
Section: Discussionmentioning
confidence: 75%
“…2). Pi concentrations need to be conserved in the roots to facilitate the acquisition of external Pi sources and upgrade the level of Pi in nodules during Pi starvation conditions (8,21), as observed with the McCP-31-inoculated plants under Pi-deficient conditions (Fig. 2).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Soybean transgenic hairy roots and nodules harboring ProGmEXPB2::GUS or CaMV35S::GUS were generated using the hypocotyl injection method as described previously (Qin et al, 2012). Roots and nodules were harvested at 7, 14, 21, 30, and 40 dai with BXYD3.…”
Section: Histochemical Gus Staining Of Tissue Sectionsmentioning
confidence: 99%
“…It has been found that phosphate (Pi) starvation-induced P transporters in rhizobia are required for symbiotic N 2 fixation (Bardin et al, 1996). In soybean, maintaining Pi homeostasis in nodules through enhanced P transporters is very important for N 2 fixation efficiency (Qin et al, 2012). Moreover, several genes such as phosphoenol pyruvate phosphatase in common bean (Bargaz, et al, 2012) and purple acid phosphatase in soybean (Li et al, 2012) are highly upregulated in nodules at low P level, implying that these genes might be involved in the adaptation of symbiosis to Pi starvation.…”
mentioning
confidence: 99%